The Potyviral Protein 6K2 from Turnip Mosaic Virus Increases Plant Resilience to Drought - Ved Prakash; Chad T. Nihranz; Clare L. Casteel (Molecular Plant-Microbe Interactions, 2023)
Virus infection can increase drought tolerance of infected plants compared with noninfected plants; however, the mechanisms mediating virus-induced drought tolerance remain unclear. In this study, we demonstrate turnip mosaic virus (TuMV) infection increases Arabidopsis thaliana survival under drought compared with uninfected plants. To determine if specific TuMV proteins mediate drought tolerance, we cloned the coding sequence for each of the major viral proteins and generated transgenic A. thaliana that constitutively express each protein. Three TuMV proteins, 6K1, 6K2, and NIa-Pro, enhanced drought tolerance of A. thaliana when expressed constitutively in plants compared with controls. While in the control plant, transcripts related to abscisic acid (ABA) biosynthesis and ABA levels were induced under drought, there were no changes in ABA or related transcripts in plants expressing 6K2 under drought compared with well-watered conditions. Expression of 6K2 also conveyed drought tolerance in another host plant, Nicotiana benthamiana, when expressed using a virus overexpression construct. In contrast to ABA, 6K2 expression enhanced salicylic acid (SA) accumulation in both Arabidopsis and N. benthamiana. These results suggest 6K2-induced drought tolerance is mediated through increased SA levels and SA-dependent induction of plant secondary metabolites, osmolytes, and antioxidants that convey drought tolerance. [Graphic: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.